2013
DOI: 10.3109/01612840.2012.758206
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Adolescent Depression: An Examination of Racial Differences

Abstract: Conventional behavior theories that assert adolescent risk behaviors are determined by peer and parental relationships are being challenged as research begins to consider broader socioenvironmental factors. This study, using data from the Longitudinal Study for Adolescent Health (Add Health), Wave II, Public Use Data, and the Social Determinants of Adolescent Risk Behaviors (SDOARB) framework, examines relationships among socioeconomic status (SES), academic performance, perceived peer prejudice, and perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…The higher prevalence of mental health symptoms for racial/ethnic minorities in pre- and early adolescence is in line with prior findings 11 and may reflect earlier pubertal timing in minority youth 22 or place-based racial/ethnic differences. 23 Additionally, findings of higher prevalence of depressive symptoms in males in early adolescence and greater escalation of symptoms from early to mid-adolescence in females are consistent with prior research. 10 …”
Section: Discussionsupporting
confidence: 83%
“…The higher prevalence of mental health symptoms for racial/ethnic minorities in pre- and early adolescence is in line with prior findings 11 and may reflect earlier pubertal timing in minority youth 22 or place-based racial/ethnic differences. 23 Additionally, findings of higher prevalence of depressive symptoms in males in early adolescence and greater escalation of symptoms from early to mid-adolescence in females are consistent with prior research. 10 …”
Section: Discussionsupporting
confidence: 83%
“…In addition, our findings suggest a need for a closer scrutiny of school-based factors that may contribute to adolescents’ substance use behaviors. We postulate, as some other researchers have, that individuals who experience prejudice and discrimination are at increased risk for substance use and other psychological problems commonly associated with substance use, such as depression, anxiety, a nd suicide (Fuller-Rowell et al, 2011; Gerrard et al, 2012; Respress, Joe, & Francis, 2012; Respress, Morris, Gary, Lewin, & Francis, in press; Tran et al, 2010). Racial minorities in particular may be at increased risk for these problems due to repeated historical exposure to racial prejudice and discrimination.…”
Section: Discussionmentioning
confidence: 79%
“…The existent literature has focused on internalizing behaviors, such as depression and suicide (Respress, 2010; Respress et al, 2012, in press). Few studies have explored substance use and discrimination in adolescents; however, among those few, adolescents who had higher perceptions of discrimination were more likely to have reported substance use within the past 30 days and their lifetime, which is also supported by the current findings (Broman, 2007; Okamoto, Ritt-Olson, Soto, Baezconde-Garbanati, & Unger, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of discrimination and buffering effects of social integration on health and wellbeing have both gained considerable attention over the past decade. Research on the health of youth is no different, and many scholarly examinations of discrimination and health focus on youth's experiences in school settings (Benner, Crosnoe, & Eccles, 2015;Cheng, Cohen, & Goodman, 2015;Greene, Way, & Pahl, 2006;Grollman, 2012;Myrick & Martorell, 2011;Respress, Morris, Gary, Lewin, & Francis, 2013;Romero, Gonzalez, & Smith, 2015;Wong, Eccles, & Sameroff, 2003). In schools, interpersonal discrimination may take on overt forms such as harassment and violence from peers, or subtle forms such as racial microagression by teachers and school administrators (Priest, Perry, Ferdinand, Kelaher, & Paradies, 2017;Romero et al, 2015).…”
Section: Socialization In Schoolsmentioning
confidence: 99%
“…Adolescents' perceptions that teachers in their school treat students fairly taps into students relationships with caring adults in the school setting, a protective factor against emotional distress (LaRusso, Romer, & Selman, 2008). For example, Larusso (2008) found that perceptions of teacher support were associated with lower levels of drug use and depressive symptoms and Respress et al (Respress, Morris, et al, 2013) reported that perceptions of teacher fairness predicted fewer depressive symptoms among White and 'Other minority' students. Additionally, it is important examine the role that perceptions of school safety play given the association between safety perceptions in other contexts and emotional distress.…”
Section: Theoretical Orientationmentioning
confidence: 99%